Weekly cycles in peak time temperatures and urban heat island intensity. (1st July 2016) - Earl, Nick; Simmonds, Ian; Tapper, Nigel
Abstract: Regular diurnal and weekly cycles (WCs) in temperature provide valuable insights into the consequences of anthropogenic activity on the urban environment. Different locations experience a range of identified WCs and have very different structures. Two important sources of urban heat are those associated with the effect of large urban structures on the radiation budget and energy storage and those from the heat generated as a consequence of anthropogenic activity. The former forcing will remain relatively constant, but a WC will appear in the latter. WCs for specific times of day and the urban heat island (UHI) have not been analysed heretofore. We use three-hourly surface (2 m) temperature data to analyse the WCs of seven major Australian cities at different times of day and to determine to what extent one of our major city's (Melbourne) UHI exhibits a WC. We show that the WC of temperature in major cities differs according to the time of day and that the UHI intensity of Melbourne is affected on a WC. This provides crucial information that can contribute toward the push for healthier urban environments in the face of a more extreme climate.